The links between business environment, economic growth and social equity: a study of African countries - Ncube, M; Soonawalla, K; Hausken, K (Taylor and Francis, 2019)
This paper examines the relationship between the business environment, economic growth, urbanization, female labor force participation, and child mortality in African countries. Our method is to estimate the dependent variables, that is, growth and development factors, regressed on various groups of independent variables, that is, business development indicators. Our results show that the business environment has an impact on these economic and social variables. Specifically, stronger economic growth is associated with improvements in the environment for starting a business. Female labor force participation improves under conditions of better contract enforcement. Decreased child mortality is likewise associated with improvements in ease of starting a business, access to permits, and contract enforcement. The rate of urbanization shows weaker correlation with business environment variables suggesting that it is driven by other broader factors. We posit policy implications based on the reported correlations and associations, tying social equity and economic benefits to strengthened business environment variables.